Crystal structure of the Lin28-interacting module of human terminal uridylyltransferase that regulates let-7 expression - Seisuke Yamashita (Nature Portfolio, 2019)
Terminal uridylyltransferase 4/7 (TUT4/7) binds to Lin28 and modifies let-7 precursor (pre-let-7) to regulate cell differentiation and proliferation. Here the authors report the crystal structure of the N-terminal Lin28-interacting module of TUT4, showing a role of the N-terminal zinc finger domain in stabilizing the Lin28:pre-let-7:TUT4 ternary complex.